A sino-orbital scissors foreign body (2005)
The case of a sino orbital foreign body from the broken tips of a pair of scissors transversing the floor of the left orbit, left maxillary sinus and left nasal cavity, and which had been left in place for two years because of financial constrains, before its surgical removal without much sequel, is presented. The need for adequate radiological investigations in all cases of head and neck trauma as well as the institution of health insurance in developing / low income economies to cater for indigent patients especially in emergency situations is highlighted.